The influence of tuck index, depth of foot-plant, and wall contact time on the velocity of push-off in the freestyle flip turn - Prins, J. H.; Patz, A. (Biomechanics and Medicine in Swimming X, 2006)
Effective turns play a critical role in the outcome of swimming competition. The purpose of the study was to investigate the effect of three variables on the velocity of the push-off during the freestyle flip turn. The variables are: (a) the distance of the hips from the wall at foot contact (Tuck Index); (b) the depth of the foot plant on the wall during push-off; and (c) wall-contact time (WCT). Twenty three collegiate swimmers participated in the study. Following underwater video-taping, 2D analyses in the saggital plane were made using Motion Analysis Software. Statistical analysis of the data found a significant, negative correlation between push-off velocity and Tuck Index. No significant correlations existed between push-off velocity and foot-plant or between "active" WCT and push-off velocities.